MassBank and RMassBank - Schymanski, Emma L. (Henry Stewart Talks, 2017)
MassBank: an open access mass spectral library, Sharing spectra worldwide, Downloadable RMassBank, Autocuration of MS/MS spectra, Recalibration, noise reduction, annotation, Upload of thousands of spectra, Enhanced interpretation and identification, SPLASH: communicate between all mass spectral resources